ENVIRONMENTAL NEWS IN MEDIA: AS SOCIAL RESPONSIBILITY AND PRODUCTION COMMODITY - Mihardja, Eli Jamilah; Azmawati, Azman Azwan; Kurnia, Ari (Jurnal InterAct, 2018)
Previous studies have suggested that mass media plays a role in raising public awareness on environmental issues (Jurin, 2010), disseminating information to the community (Campbell, 1999) and educating the public on environmental issues. Media is also an important translator of scientific information and policy for audience (Boykoff, 2009). However, there are many barriers to the media to do those, especially in Indonesia (Mihardja, 2017). This paper describes the production process of environmental stories in Indonesia's mainstream media as well as various factors that influencing this process. The description is reviewed with a discussion of Media Theory to understand the challenges and opportunities faced by the media to carry out its role to participate in efforts to maintain the quality of the environment.